Vividness of visual imagery questionnaire scores and their relationship to visual short-term memory performance. (January 2022) - Tabi, Younes Adam; Maio, Maria Raquel; Attaallah, Bahaaeddin; Dickson, Shannon; Drew, Daniel; Idris, Mohamad Imran; Kienast, Annika; Klar, Verena; Nobis, Lisa; Plant, Olivia; Saleh, Youssuf; Sandhu, Timothy Ravinder; et al.
Abstract: Mechanisms underlying visual imagery, the ability to create vivid mental representations of a scene in the absence of sensory input, remain to be fully understood. Some previous studies have proposed that visual imagery might be related to visual short-term memory (STM), with a common mechanism involving retention of visual information over short periods of time. Other observations have shown a strong relationship between visual imagery and functional activity in the hippocampus and primary visual cortex, both regions also associated with visual STM. Here we examined the relationship of visual imagery to STM and hippocampal and primary visual cortex volumes, first in a large sample of healthy people across a large age range ( N =  229 behavioural data; N =  56 MRI data in older participants) and then in patients with Alzheimer's disease and Parkinson's disease ( N =  19 in each group compared to 19 age-matched healthy controls). We used a variant of the "What was where?" visual object-location binding task to assess the quality of remembered information over short delays. In healthy people, no evidence of a relationship between the vividness of visual imagery and any visual STM performance parameter was found. However, there was a significant positive correlation between visual imagery and the volumes of the hippocampus and primary visual cortex. Although visual STM performance was significantly impaired in patients with Alzheimer's disease, their vividness of visual imagery scores were comparable to those of age-matched elderly controls and patients with Parkinson's disease. Despite hippocampal volumes also being reduced in Alzheimer's patients, there appeared to be no impact on their self-reported visual imagery. In conclusion, visual imagery was not significantly related to visual STM performance, either in healthy controls or Alzheimer's or Parkinson's disease but it was related to hippocampal and visual cortex volume in healthy people.